2019
DOI: 10.14710/jitaa.44.3.323-332
|View full text |Cite
|
Sign up to set email alerts
|

Analysis in making decision of farmer to select bull frozen semen in Indonesia

Abstract: The research objectives was to analyze the farmer’s decision in selecting breed of bull frozen semen for Artificial Insemination (AI) and determine the factors influencing the decision. There were five bull frozen semen options which simulated in this research, such as Simmental, Limousine, Ongole Grade (Peranakan Ongole / PO), Brahman, and other option. ”Other” option was used if the farmer did not recognize what breed of frozen semen was inseminated to their cow. Farmers must choose only one option of bull f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The main cows with the highest average selling price is Brangus which is a cross between Brahman Cattle and Aberdeen Angus cattle. Other cow breeds that have high selling prices were Lim-PO (Limousin-Peranakan Ongole cattle) and Sim-PO (Simmental-Peranakan Ongole cattle) [25]. The price of Peranakan Ongole cattle is generally lower than those of Simental and Limousine.…”
Section: Discussionmentioning
confidence: 99%
“…The main cows with the highest average selling price is Brangus which is a cross between Brahman Cattle and Aberdeen Angus cattle. Other cow breeds that have high selling prices were Lim-PO (Limousin-Peranakan Ongole cattle) and Sim-PO (Simmental-Peranakan Ongole cattle) [25]. The price of Peranakan Ongole cattle is generally lower than those of Simental and Limousine.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of crossbreeding involving PO cattle makes the existence of PO cattle increasingly threatened (Sutresniwati et al 2006). The crossbreeding was carried out based on economic reasons (Agustine et al 2019), high weight gain despite high production costs , and steps to improve carcass grade and commercial value (Favero et al 2019). Crossbreeding activity is feared to produce offspring that cannot adapt to environmental conditions in Indonesia and decrease reproductive ability .…”
Section: Introductionmentioning
confidence: 99%
“…Although PO cattle have a low selling price (Agustine et al 2019), however, PO cattle are reported to have the good reproductive ability (AGRI 2018), and quickly adapt to the tropical environment thorough Indonesia (Sutarno and Setyawan 2016). PO cattle are also draught animals because they have a large body size and are strong and docile (Director General of Livestock Services Indonesia 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of frozen semen used in AI, ranging from frozen semen from local cattle, such as PO (Peranakan Ongole) cattle, to European cattle, such as Simmental and Limousin. It makes farmers have to choose the right type of frozen semen for their cows [7].…”
Section: Introductionmentioning
confidence: 99%